2017
DOI: 10.1177/1941738117742906
|View full text |Cite
|
Sign up to set email alerts
|

Attention Deficit Hyperactivity Disorder: Unique Considerations in Athletes

Abstract: Context:Attention deficit hyperactivity disorder (ADHD) is a common psychiatric condition in the general population, with evidence suggesting that it may be more common among athletes.Evidence Acquisition:Literature searches were performed on PubMed, MEDLINE, and Cochrane databases for the years 2000 to 2016 utilizing the following key search terms: ADHD, ADD, guidelines, diagnosis, athlete, sports, treatment, pharmacotherapy, stimulants, risk, cardiovascular effects, concussion, and traumatic brain injury (TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(58 citation statements)
references
References 51 publications
(150 reference statements)
0
58
0
Order By: Relevance
“…In managing ADHD in elite athletes, psychosocial interventions should be used;57 these interventions may be as effective as—and should be considered an alternative to—stimulant medication in athletes with mild functional impairment 306 309 320–325. Depending on the age of the elite athlete, treatment may include: behaviour therapy or CBT; individual education plans; parent teaching/training and caregiver support; and education for athletes, families and coaches 308 321 326…”
Section: Specific Mental Health Symptoms and Disorders In Elite Athletesmentioning
confidence: 99%
See 1 more Smart Citation
“…In managing ADHD in elite athletes, psychosocial interventions should be used;57 these interventions may be as effective as—and should be considered an alternative to—stimulant medication in athletes with mild functional impairment 306 309 320–325. Depending on the age of the elite athlete, treatment may include: behaviour therapy or CBT; individual education plans; parent teaching/training and caregiver support; and education for athletes, families and coaches 308 321 326…”
Section: Specific Mental Health Symptoms and Disorders In Elite Athletesmentioning
confidence: 99%
“…Stimulants are a primary pharmacological treatment for ADHD 62 211 306 309 321 322 324 325 327. Such medications, including those in the methylphenidate and mixed amphetamine salts classes, may be ergogenic,328 329 and are misused because of the perception of performance enhancement 306 322 324 325 327 330.…”
Section: Specific Mental Health Symptoms and Disorders In Elite Athletesmentioning
confidence: 99%
“…This is of particular concern when athletes practice or compete in the heat. Stewman et al 135 also note that stimulant use is an independent risk factor for heat illness. Recently, the independent investigation into the death of University of Maryland student and football athlete Jordan McNair found that McNair was on a prescription of Vyvanse (50mg dose).…”
Section: Psychostimulant Prescriptions and Brain Injurymentioning
confidence: 99%
“…Children with neurodevelopmental disorders such as ADHD have been found to have a greater lifetime history of concussion [19,20] but this is not a consistent finding [15].…”
Section: Introductionmentioning
confidence: 96%
“…Age also plays a significant role in concussion symptom presentation with peaks occurring in young adulthood (15)(16)(17)(18)(19) years old) and those over 65 years old [12]. Among individuals older than 65, falls are responsible for more than 50% of concussions, while in young adults, motor vehicle accidents and sports-related concussions are most common [12].…”
Section: Introductionmentioning
confidence: 99%